1990
DOI: 10.2307/1130766
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Infant-Directed Speech in the First Month after Birth

Abstract: 2 experiments examined behavioral preferences for infant-directed (ID) speech over adult-directed (AD) speech in young infants. Using a modification of the visual-fixation-based auditory-preference procedure, Experiments 1 and 2 examined whether 12 1-month-old and 16 2-day-old infants looked longer at a visual stimulus when looking produced ID as opposed to AD speech. The results showed that both 1-month-olds and newborns preferred ID over AD speech. Although the absolute magnitude of the ID speech preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
328
4
9

Year Published

1997
1997
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 622 publications
(354 citation statements)
references
References 0 publications
13
328
4
9
Order By: Relevance
“…It is well known that by 4 months of age infants show a preference for IDS when compared to ADS (Cooper, Abraham, Berman, & Staska, 1997;Cooper & Aslin, 1990Pegg, Werker, & McLeod, 1992). However, it has also been shown that during the second half of the first year of life developmental changes take place in infant preferences for IDS (Newman & Hussain, 2006;Hayashi, Tamekawa, & Kiritani, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that by 4 months of age infants show a preference for IDS when compared to ADS (Cooper, Abraham, Berman, & Staska, 1997;Cooper & Aslin, 1990Pegg, Werker, & McLeod, 1992). However, it has also been shown that during the second half of the first year of life developmental changes take place in infant preferences for IDS (Newman & Hussain, 2006;Hayashi, Tamekawa, & Kiritani, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Depressed mothers do not modify their speaking style (43,44) to produce the exaggerated "motherese" that infants prefer (45)(46)(47)(48), and which can highlight speech sound differences (49). Newborns of depressed mothers fail to show face/voice preference (22) whereas older infants do not learn as well from their mothers' infant-directed speech (50).…”
Section: Discussionmentioning
confidence: 99%
“…Similar preferences also may be found in the auditory domain. Newborns prefer not only human voices to other sounds (24), and speech to nonspeech stimuli (25), but they are also biased toward the specific intonation patterns (i.e., infantdirected speech) that indicate that they are the ones who are addressed by an utterance (26).…”
Section: Discussionmentioning
confidence: 99%